Implant failure of the Compress prosthesis: a case report - Hiroshi Koike; Kunihiro Ikuta; Hiroshi Urakawa; Tomohisa Sakai; Takeo Fujito; Yoshihiro Nishida; Shiro Imagama (Journal of Medical Case Reports)
Abstract Background The Compress is designed to achieve bone formation and stability by applying pressure at the bone–implant interface, minimizing the likelihood of aseptic loosening, which is a complication of stem implants. Herein, we report two cases of implant failure using the Compress. Case presentation Case 1 describes a 36 year-old Japanese man who underwent extraarticular tumor resection, Compress arthroplasty, and reconstruction with a gastrocnemius flap after preoperative chemotherapy for a secondary malignant giant cell tumor in the right distal femur. Postoperatively, partial weight-bearing was started at 6 weeks, and full weight-bearing was allowed at 10 weeks. One year after the surgery, a fall caused implant failure. No bone formation at the implant–bone interface was observed on radiographs immediately prior to the failure. Bone formation was achieved at the interface 1 year after revision arthroplasty, and the patient was able to walk unassisted with a brace. Case 2 describes a 14 year-old Japanese boy who underwent wide surgical resection of osteosarcoma in the left tibia, Compress arthroplasty, and reconstruction with a gastrocnemius flap after preoperative chemotherapy. The postoperative weight-bearing schedule was the same as that of case 1. One year after the surgery, the patient experienced implant failure. A revision arthroplasty was performed. One year after revision surgery, the patient was able to walk unassisted. Conclusion Although the risk factors for Compress failure remain unknown, it is important to consider patient characteristics that may inhibit bone formation, implant selection, postoperative loading timing, and radiographs of bone formation at the implant interface when using the Compress.